VARIATION OF FIXED TONGUE CRIB FOR CORRECTING TONGUE THRUSTING HABIT - Rusdiana, Elly; Goenharto, Sianiwati; Asdika, Rere Gathi (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Tongue thrusting is a behavior pattern in which the tongue protrudes through the anterior incisors and pushes the anterior teeth at rest position, during speech or swallowing. This bad habit causes malocclusion, but removable or fixed tongue crib appliance can be used to eliminate it. Purpose: To know various kinds of fixed tongue crib that can be used to overcome tongue thrust habit. Review: Habit is a repeated behavior pattern in the normal development stage. Tongue thrust makes oral muscle imbalance which eventually resulted in malocclusions such as incisor protruded and open bite. Several efforts can be done to overcome this habit including speech therapy, myofunctional therapy, tongue exercise and tongue crib orthodontic appliance usage. Tongue crib is used to returns the tongue to the normal position. Various forms of tongue crib are almost the same in the way they are made by soldering the crib to the maxillary first molar band. Conclusion: Tongue thrust habit can be corrected with fixed or removable tongue crib appliances such as hybrid habit correcting appliance, tongue crib with cold cured acrylic tongue shield, fixed palatal crib with transpalatal arch, fixed tongue loops, tongue fence, and upper hay rake.